A review on the association between computer mouse design and Musculoskeletal Disorders (MSD) - Zaidi, Mohd Huzaifi; Taib, Ibrahim Adham (Universiti Malaysia Pahang, 2022)
Prolonged mouse usage is one of the main causes of computer-related musculoskeletal disorders (MSD). Mouse is one of the most common input devices to be paired with a computer. Mouse is used to point, select and click across a computer screen with minimal effort. Nevertheless, computer mouse usage has been associated with musculoskeletal disorders. Because of that, mouse designs with ergonomic characteristics and features have been designed and marketed. This review aims to list the different types of mouse designs reported in the literature, and explore the association between mouse design and musculoskeletal disorders. To achieve the objectives, a systematic search was conducted on five online databases: PubMed, Science Direct, Cochrane Library, Biomed Central and Directory of Open Access Journals (DOAJ), as well as Google search engine using several keywords. Out of 7,131 hits, 13 papers were selected for this review after undergoing multiple stages of the paper selection process. Data were then extracted and summarised into a table according to the following characteristics: 1) Title, 2) Author, 3) Year, 4) Participant, 5) Mouse design, 6) Outcome measure, 7) Findings, and 8) Association between mouse design and MSD. This review found six different types of mouse designs, all of which were reportedly better than a conventional mouse in maintaining natural posture and reducing muscle activity. Therefore, it can be concluded that there is an association between computer mouse design and musculoskeletal disorder.